Neoadjuvant therapy with chemotherapy and immune checkpoint inhibitor for laryngeal function preservation in locally advanced hypopharyngeal cancer - Wu, San-Gang; Wang, Run-Jie; Zhou, Yi; Luo, Xian-Yang (Frontiers in Immunology, 2024)
Purpose: To evaluate the efficacy and laryngeal function preservation of neoadjuvant treatment with chemotherapy and immune checkpoint inhibitor for locally advanced hypopharyngeal cancer (LAHPC).Methods: We retrospectively collected LAHPC patients who were diagnosed between February 2022 and June 2023. The patients received a combination of chemotherapy and immune checkpoint inhibitors as the neoadjuvant therapy. The response to treatment, laryngeal function preservation rate, and short-term survival were assessed.Results: A total of 20 patients were included. Of these patients, 17 (85.0%) had stage IVA-B disease. Ten (50%) and four (20%) patients achieved pathological complete response (PCR) and major pathological response (MPR) to the primary tumor, respectively. In addition, 6 patients had incomplete pathological response (IPR). In the neck, 19 patients had node-positive disease before treatment, and only 5 patients (26.4%) had PCR to regional lymph nodes. Pathologically positive lymph nodes were still observed in 14 (73.6%) patients. Significant downgrading on narrow-band imaging assessment in primary tumors was associated with a higher probability of PCR or MPR than those with IPR (92.9% vs. 33.3%, P=0.014). The overall rate of laryngeal preservation was 95.0%. No severe perioperative complications or perioperative death were found. All patients completed the recommended postoperative radiotherapy/chemoradiotherapy. The median follow-up period was 12.1 months. The 1-year progression-free survival and overall survival were 94.1% and 92.9%, respectively. During the follow-up period, all 19 patients who underwent laryngeal preservation surgery had their laryngeal function preserved.The addition of an immune checkpoint inhibitor to neoadjuvant chemotherapy effectively preserves laryngeal function without increasing complications related to surgery and postoperative radiotherapy in LAHPC.